2001
DOI: 10.5715/jnlp.8.2_19
|View full text |Cite
|
Sign up to set email alerts
|

Balancing up Efficiency and Accuracy in Translation Retrieval.

Abstract: This research looks at the effects of segment order and segmentation on translation retrieval performance for an experimental Japanese-English translation memory system. We implement a number of both bag-of-words and segment order-sensitive string comparison methods, and test each over character-based and word-based indexing. The translation retrieval performance of each system configuration is evaluated empirically through the notion of segment edit distance between the translation output and model translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The deletion-related equivalence problem found in the translation of the student translators can also be seen in (8). (8) means that Machu Picchu is one of the few major pre-Columbian ruins found nearly intact; however, the TT means that Machu Picchu is the only major pre-Columbian ruin, showing that the meaning contained in the ST is partially deleted in the TT. Such deletion influences the TL readers' understanding of the pre-Columbian ruins found nearly intact.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The deletion-related equivalence problem found in the translation of the student translators can also be seen in (8). (8) means that Machu Picchu is one of the few major pre-Columbian ruins found nearly intact; however, the TT means that Machu Picchu is the only major pre-Columbian ruin, showing that the meaning contained in the ST is partially deleted in the TT. Such deletion influences the TL readers' understanding of the pre-Columbian ruins found nearly intact.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, componential analysis is helpful to bridge the gap for culture differences [7]. In addition to human translation, other studies have also been conducted to examine the accuracy of translation performed by translation machines ( [8]; [9]; [10]). They found that, despite their small number of weaknesses, translation machines are helpful in achieving accuracy in translation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, componential analysis is helpful to bridge the gap for culture differences (Chen-Chen & Jin-Zhu, 2016). In addition to human translation, other studies have also been conducted to examine the accuracy of translation performed by translation machines (Baldwin & Tanaka, 2001;Aiken et al, 2009;Aiken & Bal-an, 2011). They found that, despite their small number of weaknesses, translation machines are helpful in achieving accuracy in translation.…”
Section: Introductionmentioning
confidence: 99%